Comparative analysis of surgical and percutaneous pulmonary valve implants over a 20-year period. (18th August 2021) - Hribernik, Ines; Thomson, John; Ho, Andrew; English, Kate; Van Doorn, Carin; Jaber, Osama; Bentham, James
Abstract: : OBJECTIVES: Since percutaneous pulmonary valve implantation (PPVI) was introduced to prolong the lifetime of surgically placed right ventricular to pulmonary artery conduits, valve technology has evolved and the indications for PPVI expanded to native and larger right ventricular outflow tracts. We explore how indications, patient populations and outcomes compare to surgical pulmonary valve replacement (PVR). METHODS: This is a retrospective cohort study of PPVI and PVR procedures between 1998 and 2020 at a single UK centre. One hundred and twenty-eight patients underwent PPVI and 365 patients PVR. Primary outcome measures were survival, infective endocarditis and reintervention. RESULTS: The most common indication for PVR was replacement of the native pulmonary valve for pulmonary regurgitation whereas PPVI was more commonly used to treat pulmonary stenosis in a previously placed bioprosthetic conduit or valve. Treatment indications for PPVI expanded over the study to include the native right ventricular outflow tract. Survival was similar for PPVI and PVR (92% PPVI and 96.8% PVR at 5 years; 85.8% PPVI and 95.1% PVR at 10 years). Preprocedural New York Heart Association class 3 and 4 was the most important predictor of poor outcome. Annualized infective endocarditis rate was significantly higher for the Melody PPVI (0.024 vs 0.0024/person/year for PVR, P < 0.05). Both groups showed significant symptomatic improvement postprocedure with remodelling of ventricular volumes and improvement in cardiac output. Long-term follow-up for PVR showed half of patients will need replacement at 10–15 years post-index procedure. CONCLUSIONS: An increasing number of patients requiring PVR can now be treated percutaneously. A lifetime strategy for re-valving should be considered at the first valve implant. Abstract : Many patients with repaired congenital heart disease have dysfunctional or absent pulmonary valves, or a right ventricle (RV) to pulmonary artery (PA) conduit.